Challenges And Influences on Araling Panlipunan Instruction In Eastern Kayapa Public Secondary Schools - Otto, Diane Dawn (International Journal of Sustainability and Advanced Integrated Research, 2026)
Social Studies are crucial for developing learners who are globally competitive, socially responsible, and culturally aware. This study took a closer look at the challenges and factors influencing Araling Panlipunan instruction in Eastern Kayapa Public Secondary Schools during the 2025–2026 school year. The main goals were to evaluate how effective the teaching practices were, identify the obstacles teachers faced, explore the interventions used to tackle these challenges, and examine how interpersonal relationships and assessment tools interact in teaching Araling Panlipunan. The research used a quantitative descriptive-correlational design, gathering data from 30 Araling Panlipunan teachers through a validated, researcher-made questionnaire. To analyze the data, methods like frequency count, percentage, weighted mean, standard deviation, Pearson Product-Moment Correlation, and simple linear regression were employed. The results showed that Araling Panlipunan instruction was generally effective, especially regarding teachers’ competence, instructional strategies, interpersonal relationships, and assessment tools. While teachers generally saw the barriers as not too serious, classroom management was noted as a slightly bigger issue. Teachers often used learner-centered interventions, positive discipline, and remedial instruction to boost student learning and participation. Moreover, the findings highlighted a significant positive link between interpersonal relationships and assessment tools, indicating that positive classroom relationships can lead to more effective assessment practices. The study concluded that effective teaching practices, supportive classroom relationships, and suitable interventions play a significant role in enhancing the quality of Araling Panlipunan instruction and student learning outcomes in public secondary schools.